Valuing as a social process: Embodiment, relevance, and commensuration - Stefan Ecks (Finance and Society, 2023)
In Inventing Value, Dave Elder-Vass (2022) argues that value is a set of beliefs about items that are strategically propagated to increase profits. The emphasis on value as a social process is particularly welcome, as this is the most fruitful direction for understanding worth. But the book leaves most of the important questions unanswered: who or what creates value, how to distinguish real and fake value, or how value can be best created and redistributed, are all left out of the discussion. A general theory of value remains elusive.
Keywords: 300; asset circles; financial value; redistribution; social conventions; Value; value creation